Elektrokemijske in površinsko analitične raziskave trdih nitridnih prevlek - Milošev, Ingrid (Vakuumist, 1997)
Generally, transition metal nitrides axhibit high hardness, high melting point, good electrical and thermal conductivity, as well as chemical stability. Within the last decade the transition metal nitride coatings have been increasingly used for wear protection of various tools and machine components. Among these materials the industrial use of TiN has been widely accepted, although recently interesting properties of other nitride coatings have becoming recognized, e.g. CrN, TiCrN, TiAlN. In the present work the corrosion resistance of several nitrides has been investigated in aqueous solutions, as well as at elevanted temperatures. Several selected studies carried out by electrochemical methods in conjunction with surface analysis techniques (XPS, AES, EDS, SEM, AFM) are presented.
Keywords: trde prevleke; elektrokemija; površinska kemija; površine; korozija